The Future of business process management: robotic process automation - Liao, Han; Dalbir Singh,; Ma, Jiqiao; Hu, Xuting (Penerbit Universiti Kebangsaan Malaysia, 2024)
With increasing globalisation, organisations are confronted with intensifying market competition. Consequently, organisations continually implement novel technologies to address the challenges posed by market competition. In business process management (BPM), robotic process automation (RPA) is regarded as a tool or methodology that can automate specific tasks or activities within a business process. RPA is widely employed as a standard solution in various industries to assist enterprises in automating their processes, enhancing their operational efficiency, and reducing operational costs. Nevertheless, it is prudent to consider which processes can be automated by applying RPA and the most appropriate deployment methods for RPA. A literature review reveals that process identification is the optimal method for identifying processes suitable for automation, and three approaches - process mining, process quality-based and interview-based can be considered. There are three principal models for deploying RPA: local, cloud and hybrid. The RPA managers in an organisation are thus able to select the most appropriate deployment option based on the organisation's policies, requirements, and cost considerations. Furthermore, this study identifies the critical success factors (CSFs) and analyses their relationships using a 'why-why' diagram. This study could assist organisations in a more comprehensive understanding of RPA technology, which enables more effective utilisation of RPA for enhanced process management.